Fundamentals of Entrepreneurship ETR300 Sate Kita Cafe / Aimi Athirah Abdullah... [et al.] - Abdullah, Aimi Athirah; Sulainan, Sheril Faiznur; Spawi, Zulkifli; Morshidi, Aldrina; Julai, Nur Syakirin (2019)
The name of our company is SATE KITA CAFE. The business is in form of PARTERSHIP which consists of five members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is selling Sate and Nasi Impit. Our business operation is at 7.00 am to 5.00 pm every Monday to Saturday and off day on Sunday. However, we would change the business operation in the fasting month. We would only start the operation at 4.00 pm until 9.00 pm. The purpose of changing our business operation is to allow our customer to buy Sate Kita to breaks their fast later. Besides, it is also to respect the month of Ramadhan itself. There are no sleeping partners and all are entitled to participate in the business management. We agreed that Aimi Athirah binti Abdullah is our General Manager, Sheril Faiznur binti Sulainan is the Administration Manager, Zulkifli bin Spawi is the Operation Manager, Aldrina binti Morshidi as Financial Manager and Nur Syakirin binti Julai as our Marketing Manager. The selection of General Manager is based on consensus among all the partners and selected based on the amount of capital that she contributed in the business. The management team will be lead by the General Manager and assist by the other managers. The General Manager is responsible in planning, leading, controlling and organizing the business. The Administration Manager is responsible for the job that related to administration such as planning and arranging the remuneration schedule of salary and wages. The Operation Manager is responsible to the entire job that related to the operation and will be supervise and coordinate the operation of the business. The Marketing Manager will be responsible to create the marketing plan, identifying the customer’s need and demand, identifying the competitors, target market, market size and forecast the future market. Lastly, the Financial Manager will be handled the financial matters such as preparing the budget and financial statement for expenses of each departments and controlling the flow of the money of the organization.